2021
DOI: 10.1155/2021/2427427
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Hypoxia-Related Gene Profiling Characterizes Clinicopathological Features and Immune Status of Mismatch Repair-Deficient Colon Cancer

Abstract: Despite dramatic responses to immune checkpoint inhibitors (ICIs) in patients with colon cancer (CC) harboring deficient mismatch repair (dMMR), more than half of these patients ultimately progress and experience primary or secondary drug resistance. There is no useful biomarker that is currently validated to accurately predict this resistance or stratify patients who may benefit from ICI-based immunotherapy. As hypoxic and acidic tumor microenvironment would greatly impair tumor-suppressing functions of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…HALLMARK_HYPOXIA: This gene signature contained 200 genes and could be searched in GSEA database (http://www.gsea-msigdb.org/gsea/msigdb/cards/HALLMARK_HYPOXIA.html) [11]. It has been identi ed to be related to the clinicopathological features and immune status of colorectal cancer in our previous studies [12,13].…”
Section: Construction Of the Multiple Gene Signatures Listmentioning
confidence: 99%
“…HALLMARK_HYPOXIA: This gene signature contained 200 genes and could be searched in GSEA database (http://www.gsea-msigdb.org/gsea/msigdb/cards/HALLMARK_HYPOXIA.html) [11]. It has been identi ed to be related to the clinicopathological features and immune status of colorectal cancer in our previous studies [12,13].…”
Section: Construction Of the Multiple Gene Signatures Listmentioning
confidence: 99%
“…Transcriptomic profiling of MSI-H/dMMR gastrointestinal tumors showed that hypoxia-related signaling pathways were upregulated in ICI nonresponders ( 76 ). Recently, several studies proposed that hypoxia-related genes can be classified as predicting immune cell infiltration and prognosis of colon cancer patients ( 25 , 28 , 150 ). These genes provide potential therapeutic targets for immunotherapy as well as prognostic biomarkers for colon cancer patients.…”
Section: Other Gene Signatures Of the Tme As Predictive Biomarkers Fo...mentioning
confidence: 99%